Answer:
f(n) =
![a_(n)= -34 + 12(n-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/zdhzp0i86vylcingwovvsxme7ns6eko0lb.png)
Explanation:
The explicit form of an arithmetic sequence is given by the formula:
![a_(n)=a_(1) + d(n-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/2vge2d9tgb0t47x9g7f8ullsiembq2bbqt.png)
an= nth term
a1= first term
d= common difference
In this case, a1= -34
In order to obtain the value of the common difference you have to subtract two consecutive terms of the sequence (The largest minus the smallest)
-22 - (-34) = 12
To confirm that it's the common difference, subtract another two consecutive terms:
-10 - (-22) = 12
Therefore d=12
Replacing in the formula:
![a_(n)= -34 + 12(n-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/zdhzp0i86vylcingwovvsxme7ns6eko0lb.png)